Three new species of acanthocephalans (Palaeacanthocephala) from marine fishes collected off the East Coast of South Africa - Lisitsyna, Olga I; Kudlai, Olena; Cribb, Thomas H; Smit, Nico J (Folia parasitologica, 2019)
Three new species of acanthocephalans are described from marine fishes collected in Sodwana Bay, South Africa: Rhadinorhynchus gerberi n. sp. from Trachinotus botla (Shaw), Pararhadinorhynchus sodwanensis n. sp. from Pomadasys furcatus (Bloch et Schneider) and Transvena pichelinae n. sp. from Thalassoma purpureum (Forsskål). Transvena pichelinae n. sp. differs from the single existing species of the genus Transvena annulospinosa Pichelin et Cribb, 2001, by the lower number of longitudinal rows of hooks (10-12 vs 12-14, respectively) and fewer hooks in a row (5 vs 6-8), shorter blades of anterior hooks (55-63 vs 98), more posterior location of the ganglion (close to the posterior margin of the proboscis receptacle vs mid-level of the proboscis receptacle) and smaller eggs (50-58 × 13 µm vs 62-66 × 13-19 µm). Pararhadinorhynchus sodwanensis n. sp. differs from all known species of the genus by a combination of characters. It closely resembles unidentified species Pararhadinorhynchus sp. sensu Weaver and Smales (2014) in the presence of a similar number of longitudinal rows of hooks on the proboscis (16-18 vs 18) and hooks in a row (11-13 vs 13-14), but differs in the position of the lemnisci (extend to the level of the posterior end of the proboscis receptacle or slightly posterior vs extend to the mid-level of the receptacle), length of the proboscis receptacle (910-1180 µm vs 1,460 µm) and cement glands (870-880 µm vs 335-350 µm). Rhadinorhynchus gerberi n. sp. is distinguishable from all its congeners by a single field of 19-26 irregular circular rows of the tegumental spines on the anterior part of the trunk, 10 longitudinal rows of hooks on the proboscis with 29-32 hooks in each row, subterminal genital pore in both sexes, and distinct separation of the opening of the genital pore from the posterior edge of the trunk (240-480 μm) in females. Sequences for the 18S rDNA, 28S rDNA and cox1 genes were generated to molecularly characterise the species and assess their phylogenetic position. This study provides the first report based on molecular evidence for the presence of species of Transvena Pichelin et Cribb, 2001 and Pararhadinorhynchus Johnston et Edmonds, 1947 in African coastal fishes.
Keywords: Sequence Analysis, DNA; Microscopy, Electron, Scanning; Prevalence; Acanthocephala; South Africa; DNA; morphology; mikroskopie elektronová rastrovací; mužské pohlaví; prevalence; Helminthiasis, Animal; helmintózy zvířat; Sodwana Bay; Rhadinorhynchus; Echinornhynchida; ženské pohlaví; zvířata; Transvena; nemoci ryb; fylogeneze; Pararhadinorhynchus; Host-Parasite Interactions; Jihoafrická republika; sekvenční analýza DNA; interakce hostitele a parazita; Fish Diseases; Fishes; Perciformes; ryby; Female; Phylogeny; Male; Animals